Pengembangan Media Miniatur Pembangkit Listrik Tenaga Air (PLTA) Pada Pembelajaran IPA Kelas IV Sekolah Dasar - Silvina Noviyanti; Hamidi Hamidi (Jurnal Gentala Pendidikan Dasar, 2019)
This study aims to develop learning media for miniature energy sources of hydroelectric power plants, to determine the validity and practicality of hydropower media. This type of research uses the ADDIE development model (analysis, design, development, implementation, evaluation.) This media was developed and then validated by the validator, including the validation of media experts and learning experts. From the results of the validation, the expert team can find out the feasibility level of the product made. After obtaining the results of validation, then the individual trials were carried out and a small group trial was conducted to determine the practicality of learning media for mini energy sources from the 4th grade hydroelectric elementary school. This researcher has produced a product in the form of a miniature PLTA energy source learning media with the theme of always saving energy, sub-themes of energy sources, learning 2, the contents of the competency learning energy class IV SD energy learning. Learning media for PLTA miniature energy sources developed can be used as learning support media, research is expected to be carried out in order to develop a variety of learning media that are more interesting.